Pengelolaan Retribusi Pasar Di Dinas Perindustrian Dan Perdagangan Kabupaten Bandung - Gilang Aprilianto; Faizal Pikri; Fitri Pebriani Wahyu (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2022)
Based on the results of the study, the authors suspect that the management of user fees is not optimal, this can be seen from the number of traders who do not pay market fees. UPTD and Disperindag have difficulty in anticipating this. So even when viewed from the point of view of the results (effectiveness) of the management of this market retribution, it is still estimated that the collection is not optimal. The researcher wants to use the theory of financial management by Nick Devas (1989) which has five dimensions regarding the management of market charges which include simple, complete, efficient, effective, and easy to adjust. The method used in this study uses a descriptive method with a qualitative approach. The type of data used in this research is using quantitative and qualitative data. The data sources used are primary and secondary data sources. The locus of this research is in the Department of Industry and Trade, Bandung Regency. The sample selection technique used is purposive sampling which is this technique to determine the informant with the best position in providing the information needed. For data analysis, the researcher uses the theory of Miles and Huberman's model which says that qualitative data analysis is carried out in an interactive way and continues continuously until it is finished, until the data is saturated. The results showed that the Market Levy Financial Management at the Industry and Trade Service was not fully optimal. Because in terms of results (effectiveness) there are still many problems that need to be faced and resolved by local governments.